Efek Pemberian Premedikasi Deksametason Terhadap Durasi Rokuronium Dibanding Placebo pada Anestesi Umum Intubasi - Adi, Danis Woro Kuncoro; Uyun, Yusmein; Apsari, Ratih Kumala Fajar (Jurnal Komplikasi Anestesi, 2020)
Background: Dexamethasone is often used as prevention and treatment for postoperative nausea and vomiting, reducing the severity of postoperative pain and analgesic requirements. The study of dexamethasone effects on the rocuronium duration might be beneficial in patients who have contraindications to neostigmine or atropine reversal. Purpose: To evaluate the relation between rocuronium duration with dexamethasone premedication compare with placebo in patient with general anesthesia intubation procedure with rocuronium neuromuscular blocking agent in GBST RSUP Dr. Sardjito. Methods: An experimental research design, randomized clinical trial with double blind. The sample was chosen using the non-probability sampling method in a consecutive manner in 3 months. Sample was divided into two groups: group receiving dexamethasone premedication and group receiving placebo NaCl 0.9%. Time monitoring starts after the TOF shows the number 0 until it reaches TOF 0.9. Results: The study was conducted on 58 research subjects. Numeric data was analysed using independent T test and categorical data was analysed using chi square. Dexamethasone premedication was found to reduce the duration of rocuronium with the time needed to reach TOF 0.9 was 111±14.33 minutes compared with 123±14.57 minutes in the placebo group (P = 0.003). Conclusion: Dexamethasone premedication shortens the duration of rocuronium compared to the administration of placebo under intubation general anesthesia.